The Gut Microbiota-Host Partnership as a Potential Driver of Kawasaki Syndrome - Esposito, Susanna; Polinori, Ilaria; Rigante, Donato (Frontiers in Pediatrics, 2019)
Kawasaki syndrome (KS) is a necrotizing vasculitis of small- and medium-sized vessels mostly affecting children under 5 years of age: a host of clinical and epidemiological data supports the notion that KS might result from an infectious disease. However, so many efforts have failed to identify a potentially universal trigger of KS. The contribution of the intestinal microbial community called “microbiota” to KS has been evaluated by an increasing number of studies, though limited to small cohorts of patients. Differences in the microbiota composition were found in children with KS, both its acute and non-acute phase, with abnormal colonization by Streptococcus species in the intestinal tract and a wider presence of Gram-positive cocci in jejunal biopsies. In particular, a higher number of Gram-positive cocci (of the genera Streptococcus and Staphylococcus), Eubacterium, Peptostreptococcus, HSP60-producing Gram-negative microbes has been found in the stools of KS children and their effects on the antigenic repertoire of specific T cells and Vβ2 T cell expansion have been assessed. Conversely, Lactobacilli were lacking in most children with KS compared with other febrile illnesses and healthy controls. Nowadays, all studies available have confirmed that an imbalance in the gut microbiota might indirectly interfere with the normal function of innate and adaptive immunity, and that variable microbiota interactions with environmental factors, mainly infectious agents, might selectively drive the development of KS in genetically susceptible children. Further investigations of the intestinal microflora in larger cohorts of KS patients will provide clues to disentangle the pathogenesis of this disease and probably indicate disease-modifying agents or more rational KS-specific therapies.